Flue gas treatment process

By attaching a specific polymer film layer and grafted carbon nanotubes to the surface of the dust removal filter bag, the problems of dust adhesion and electrostatic adsorption in flue gas treatment are solved, and the excellent waterproof, oil-proof and anti-static properties of the dust removal filter bag are achieved. Extended service life.

CN119327268AActive Publication Date: 2025-01-21JIANGSU CTIEC ENVIRONMENTAL PROTECTION RES INST
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411449660.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

During the flue gas treatment process, the water vapor and oily substances in the flue gas after denitrification lead to an increase in the viscosity of dust, which easily covers the surface of the dust removal filter bag, causing the phenomenon of pasting bags, and the electrostatic effect of the dust particles makes it difficult to remove.

Method used

On the surface of the dust removal filter bag is attached a polymer film layer obtained by the copolymerization of amidates of enyl stearate, acryloyl ethylene diamine, acryloyl chloride and γ-aminopropyl trialkoxysilane, and is coated with acryloyl ethylene diamine. It is grafted with carbon nanotubes to improve waterproof, oil-proof and anti-static properties.

Benefits of technology

It effectively prevents dust from adhering to the surface of the dust filter bag, avoids the occurrence of bag paste, and extends the service life of the dust filter bag.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a flue gas treatment process, and belongs to the technical field of flue gas treatment, and the process comprises the following steps: introducing flue gas into an SCR (Selective Catalytic Reduction) reactor, and carrying out denitration treatment on the flue gas by utilizing ammonia gas and a denitration catalyst to obtain denitrated flue gas; the denitrated flue gas enters a dust remover, dust removal is conducted on the denitrated flue gas through a dust removal filter bag, and dust-removed flue gas is obtained; wherein a polymer film layer is attached to the surface of the dust removal filter bag, and the polymer film layer is obtained by copolymerization of vinyl stearate, acryloyl ethylenediamine, acryloyl chloride and an amidate of gamma-amino propyl trialkoxysilane; a carbon nano tube is grafted on the acryloylethylenediamine; and the dedusted flue gas is introduced into the desulfurization tower for desulfurization treatment and then is led out to be discharged. The polymer film layer attached to the surface of the dust removal filter bag is used for improving the waterproof, oil-proof and anti-static capabilities of the dust removal filter bag, and the phenomenon of bag pasting can be effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flue gas treatment process and belongs to the technical field of flue gas treatment. Background Art

[0002] Selective Catalytic Reduction (SCR) refers to the process of selectively reducing NO in flue gas using a reducing agent (such as NH3) under the action of a catalyst. x The reaction produces non-toxic and non-polluting N2 and H2O. Selectivity refers to the fact that the flue gas denitrification catalyst selectively converts NO x Reduced to nitrogen, while very little SO2 in the flue gas is oxidized to SO3.

[0003] The flue gas after denitration contains a lot of dust, which needs to be dedusted before desulfurization and discharge. However, water vapor will be generated during the flue gas denitration process, and the presence of this water vapor will make the dust stickier. After contacting the dust filter bag, due to the strong intermolecular force, it will cover the surface of the dust filter bag, causing the bag to stick; at the same time, the oily substances contained in the flue gas will also cause the bag to stick after mixing with the dust; and under the action of airflow or electric field, static electricity will be generated between dust particles, making the particles more easily adsorbed on the surface of the dust filter bag, making it difficult to remove. Summary of the invention

[0004] The object of the present invention is to provide a flue gas treatment process, which utilizes the polymer film layer attached to the surface of the dust filter bag to improve the waterproof, oil-proof and anti-static capabilities of the dust filter bag, and can effectively prevent the occurrence of bag sticking.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A flue gas treatment process, the process is as follows:

[0007] S1. Flue gas is introduced into the SCR reactor, and ammonia and a denitration catalyst are used to denitrate the flue gas to obtain denitrated flue gas;

[0008] S2, the flue gas after denitration enters the dust collector, and the dust removal filter bag is used to remove dust from the flue gas after denitration to obtain dust-removed flue gas;

[0009] The surface of the dust filter bag is attached with a polymer film layer obtained by copolymerization of stearic acid ethylenediamine, acryloyl chloride and γ-aminopropyltrialkoxysilane amidate; and carbon nanotubes are grafted on the acryloylethylenediamine;

[0010] S3. The flue gas after dust removal is introduced into the desulfurization tower for desulfurization treatment and then discharged to the outside.

[0011] Preferably, the method for preparing the polymer in the polymer film layer comprises the following steps:

[0012] Step 1, under a nitrogen atmosphere, dispersing acryloyl chloride and γ-aminopropyltrialkoxysilane in a triethylamine solution, stirring and heating to react, to obtain an amidate of acryloyl chloride and γ-aminopropyltrialkoxysilane;

[0013] Step 2, continue to add stearic acid ethylenediamine and acryloylethylenediamine into the reaction system of step 1, then dropwise add initiator and stir and heat to react to obtain a polymer intermediate;

[0014] Step 3, adding the carboxyl-modified carbon nanotube solution into the reaction system of step 2, and continuing the reaction to obtain a polymer;

[0015] The molar ratio of acryloyl chloride, γ-aminopropyltrialkoxysilane, triethylamine, stearic acid ester, acryloylethylenediamine and initiator is 1:(1-1.2):(0.2-0.5):(1-3):(1.5-2.5):(0.05-0.2);

[0016] The mass ratio of acrylamide to carboxyl-modified carbon nanotubes is 1:(1.1-1.3).

[0017] Preferably, the stearic acid olefin ester is vinyl stearate and / or allyl stearate;

[0018] The γ-aminopropyltrialkoxysilane is γ-aminopropyltrimethoxysilane and / or γ-aminopropyltriethoxysilane;

[0019] The initiator is AIBN.

[0020] Preferably, the solvents used in the triethylamine solution and the carboxyl-modified carbon nanotube solution are both DMF;

[0021] In the triethylamine solution, the content of triethylamine is 0.1-0.5 mol / L;

[0022] In the carboxyl-modified carbon nanotube solution, the content of the carboxyl-modified carbon nanotube is 80-120 g / L.

[0023] Preferably, in step 1, the stirring and heating reaction conditions are: 50-200 rpm, 40-50° C., 2-5 h.

[0024] Preferably, in step 2, the stirring and heating reaction conditions are: 100-300 rpm, 60-80° C., 3-7 h.

[0025] Preferably, in step 3, the reaction conditions are: 100-300 rpm, 60-80° C., 1-3 h.

[0026] Preferably, the preparation method of carboxyl-modified carbon nanotubes is:

[0027] Carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid are mixed in a mass ratio of (1-5):(8-15):(2-5), and then shaken and mixed at 30-70° C. for 3-5 hours, filtered, washed and dried to obtain carboxyl-modified carbon nanotubes.

[0028] Preferably, the preparation method of the dust removal filter bag with a polymer film layer attached to the surface is:

[0029] The polymer is dispersed in water to prepare a 15-30% emulsion, and then the cloth is immersed in the emulsion, dipped and rolled, the rolling rate is 80-90%, and then baked at 110-125°C for 3-5 minutes to obtain the treated cloth, and then cut, sewed and assembled to obtain a dust filter bag.

[0030] Preferably, the raw material of the cloth is any one of polyester, aramid, PPS, PP and PTFE.

[0031] The beneficial effects of the present invention are:

[0032] The polymer film layer component contains a polymer obtained by copolymerization of stearic acid ester, acryloylethylenediamine, and an amidate of acryloyl chloride and γ-aminopropyltrialkoxysilane, wherein stearic acid ester, acryloylethylenediamine, and an amidate of acryloyl chloride and γ-aminopropyltrialkoxysilane are copolymerized through carbon-carbon double bonds, and the free radical copolymerization is a ignored copolymerization, so the CC main chain of the polymer, the long-chain alkyl side chain in stearic acid ester, and the siloxane structure in the side chain of the amidate of acryloyl chloride and γ-aminopropyltrialkoxysilane can be fully dispersed in the polymer film layer to form a waterproof network; at the same time, after the polymer is dispersed in water and impregnated into the dust filter bag fabric, a polysiloxane structure with a strong hydrogen bond with the dust filter bag fabric will be formed to improve the adhesion effect.

[0033] The amide structure in acrylamide, the amide structure formed between acrylamide and carboxyl-modified carbon nanotubes, and the amide structure in the amidate of acryloyl chloride and γ-aminopropyltrialkoxysilane have a good oil-repellent effect. Also, due to the blind copolymerization of free radicals, the amide structure will be fully dispersed in the polymer film layer to form an oil-repellent network. The carbon nanotubes grafted with acrylamide will follow the acrylamide to be fully dispersed in the polymer to form a conductive network, thereby improving the antistatic effect and the thermal stability of the dust filter bag. DETAILED DESCRIPTION

[0034] The present invention will be specifically described below in conjunction with the embodiments.

[0035] Example 1: This example provides a flue gas treatment process, the process is as follows:

[0036] S1. Flue gas is introduced into the SCR reactor under the action of the induced draft fan, and ammonia is sprayed into the air intake pipe of the SCR reactor by the ammonia spraying system to mix ammonia with flue gas. Under the catalysis of the denitration catalyst in the SCR reactor, nitrogen oxides in the flue gas generate nitrogen and water, thereby reducing the content of nitrogen oxides in the flue gas and reducing the pollution of the flue gas to the environment, thereby achieving denitration and obtaining denitrated flue gas.

[0037] S2. The flue gas after denitrification enters the dust collector under the action of the induced draft fan, and the dust removal filter bag is used to remove the dust from the flue gas after denitrification to obtain the dust-removed flue gas.

[0038] Since water vapor is generated during the flue gas denitrification process, the presence of this water vapor will cause the dust to become more sticky. After coming into contact with the dust filter bag, due to the strong intermolecular force, it will cover the surface of the dust filter bag, causing the bag to become sticky. At the same time, the oily substances contained in the flue gas will also cause the bag to become sticky after mixing with the dust. Moreover, under the airflow, static electricity will be generated between the dust particles, making the particles more easily adsorbed on the surface of the dust filter bag, making it difficult to remove.

[0039] Therefore, in this embodiment, the dust filter bag is modified, and a polymer film layer obtained by copolymerization of stearic acid ester, acryloylethylenediamine, and acryloyl chloride and γ-aminopropyltrimethoxysilane is attached to the surface of the dust filter bag; and carbon nanotubes are grafted on the acryloylethylenediamine; the raw material of the fabric of the dust filter bag is polytetrafluoroethylene (PTFE).

[0040] Specifically, the preparation method of the dust removal filter bag with a polymer film layer attached to the surface is:

[0041] Step 1: Under nitrogen atmosphere, 0.5 mol (68.25 g) of acryloyl chloride and 0.55 mol (136.07 g) of γ-aminopropyltrimethoxysilane are dispersed in a triethylamine solution (1 L of N,N-dimethylformamide (DMF) as solvent; the amount of triethylamine added is 10.21 g), and the mixture is reacted at 45 ° C for 4 h at a stirring rate of 100 rpm to obtain an amidate of acryloyl chloride and γ-aminopropyltrimethoxysilane.

[0042] Step 2: Continue to add 0.75 mol (165 g) of vinyl stearate and 0.75 mol (82.61 g) of ethylenediamine to the reaction system of step 1, then dropwise add 0.05 mol (8.2 g) of azobisisobutyronitrile (AIBN) and react at 200 rpm and 80° C. for 5 h to obtain a polymer intermediate.

[0043] Step 3: Mix carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 1:8:2, shake and mix at 50°C for 4 hours, filter, wash (wash with water until neutral), and dry (70°C, 3 hours) to obtain carboxyl-modified carbon nanotubes; add carboxyl-modified carbon nanotube solution (1L of N,N-dimethylformamide (DMF) as solvent; the amount of carboxyl-modified carbon nanotubes added is 91g) to the reaction system of step 2, and continue the reaction at 80°C at 200rpm for 2 hours to obtain a polymer.

[0044] Step 4: Disperse the polymer obtained in step 3 in 50°C water to prepare a 15% emulsion, then soak the polytetrafluoroethylene cloth in the emulsion for 1 minute, double-dip and double-roll, with a rolling rate of 85%, and then bake at 110°C for 3 minutes to obtain the treated cloth, which is then cut, sewn, and assembled to obtain a dust filter bag with a polymer film layer attached to the surface.

[0045] S3. After dust removal, the flue gas is introduced into the desulfurization tower for desulfurization treatment under the action of the induced draft fan. The desulfurization treatment can be carried out by conventional desulfurization means. After desulfurization, the flue gas is discharged to the outside of the chimney through the induced draft fan.

[0046] Embodiment 2: It is basically the same as Embodiment 1, except that the raw material of the cloth of the dust filter bag is polyester, and the preparation method of the dust filter bag with a polymer film layer attached to the surface is also different.

[0047] Specifically, the preparation method of the dust removal filter bag with a polymer film layer attached to the surface in this embodiment is:

[0048] Step 1: Under nitrogen atmosphere, 0.5 mol (68.25 g) of acryloyl chloride and 0.6 mol (154.32 g) of γ-aminopropyltriethoxysilane were dispersed in a triethylamine solution (1 L of N,N-dimethylformamide (DMF) as solvent; the amount of triethylamine added was 10.21 g), and the mixture was reacted at 45 ° C for 4 h at a stirring rate of 100 rpm to obtain an amidate of acryloyl chloride and γ-aminopropyltriethoxysilane.

[0049] Step 2: Continue to add 1 mol (172.26 g) of allyl stearate and 0.75 mol (82.61 g) of ethylenediamine into the reaction system of step 1, then dropwise add 0.05 mol (8.2 g) of azobisisobutyronitrile (AIBN) and react at 200 rpm and 80° C. for 5 h to obtain a polymer intermediate.

[0050] Step 3: Mix carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 1:8:2, shake and mix at 50°C for 4 hours, filter, wash (wash with water until neutral), and dry (70°C, 3 hours) to obtain carboxyl-modified carbon nanotubes; add carboxyl-modified carbon nanotube solution (1L of N,N-dimethylformamide (DMF) as solvent; the amount of carboxyl-modified carbon nanotubes added is 99g) to the reaction system of step 2, and continue the reaction at 80°C at 200rpm for 2 hours to obtain a polymer.

[0051] Step 4: Disperse the polymer obtained in step 3 in 50°C water to prepare a 20% emulsion, then soak the polyester cloth in the emulsion for 1 minute, double-dip and double-roll, with a rolling rate of 90%, and then bake at 115°C for 3 minutes to obtain the treated cloth, which is then cut, sewn, and assembled to obtain a dust filter bag with a polymer film layer attached to the surface.

[0052] Performance testing:

[0053] Water repellency: measured in Y(B)813 fabric water viscosity tester according to AATCC-227 standard and method, taking the average of 2 times, 0 points is the worst and 100 points is the best;

[0054] Oil repellency: tested according to FZ / TO1067-1999 standard, 8 is the best and 1 is the worst;

[0055] Antistatic performance: The fabric is tested according to the charge surface density method in GB / T 12703.1-2008 "Evaluation of electrostatic properties of textiles".

[0056] The dust filter bag fabrics used in Example 1 and Example 2 were cut according to the above-mentioned testing standards and / or methods, and then placed in the emulsions obtained in Example 1 and Example 2 to carry out the treatment processes of the dust filter bag fabrics in Example 1 and Example 2. The obtained products were named 1# fabric and 2# fabric, respectively. The obtained test results are shown in Table 1.

[0057] Table 1 Performance test results

[0058] Waterproof(points) Oil proof(grade) <![CDATA[Surface charge density (μC·m -2 )]]> 1# cloth 90 7 0.056 2# cloth 100 7 0.068

[0059] It can be seen from the data in Table 1 that the polymer provided by the present invention can give the dust filter bag fabric excellent waterproof, oil-proof and antistatic properties, thereby preventing dust from adhering to the surface of the dust filter bag and causing bag sticking, and can extend the service life of the dust filter bag.

[0060] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A flue gas treatment process, characterized in that: The denitration process is as follows: S1. Flue gas is introduced into the SCR reactor, and ammonia and a denitration catalyst are used to denitrate the flue gas to obtain denitrated flue gas; S2, the flue gas after denitration enters the dust collector, and the flue gas after denitration is dedusted by a dust removal filter bag to obtain dust-removed flue gas; wherein, a polymer film layer obtained by copolymerization of stearic acid ethylene ester, acryloylethylenediamine, and acryloyl chloride and γ-aminopropyltrialkoxysilane is attached to the surface of the dust removal filter bag; and carbon nanotubes are grafted on the acryloylethylenediamine; S3. The flue gas after dust removal is introduced into the desulfurization tower for desulfurization treatment and then discharged to the outside.

2. A flue gas treatment process according to claim 1, characterized in that: The method for preparing the polymer in the polymer film layer comprises the following steps: Step 1, under a nitrogen atmosphere, dispersing acryloyl chloride and γ-aminopropyltrialkoxysilane in a triethylamine solution, stirring and heating to react, to obtain an amidate of acryloyl chloride and γ-aminopropyltrialkoxysilane; Step 2, continue to add stearic acid ethylenediamine and acryloylethylenediamine into the reaction system of step 1, then dropwise add initiator and stir and heat to react to obtain a polymer intermediate; Step 3, adding the carboxyl-modified carbon nanotube solution to the reaction system of step 2, continuing the reaction to obtain a polymer; wherein the molar ratio of acryloyl chloride, γ-aminopropyltrialkoxysilane, triethylamine, stearic acid ethyl ester, acryloylethylenediamine and initiator is 1:(1-1.2):(0.2-0.5):(1-3):(1.5-2.5):(0.05-0.2); The mass ratio of acrylamide to carboxyl-modified carbon nanotubes is 1:(1.1-1.3).

3. A flue gas treatment process according to claim 2, characterized in that: The stearic acid olefin ester is vinyl stearate and / or allyl stearate; The γ-aminopropyltrialkoxysilane is γ-aminopropyltrimethoxysilane and / or γ-aminopropyltriethoxysilane; The initiator is AIBN.

4. A flue gas treatment process according to claim 2, characterized in that: The solvents used in the triethylamine solution and the carboxyl-modified carbon nanotube solution are both DMF; and In the triethylamine solution, the content of triethylamine is 0.1-0.5 mol / L; In the carboxyl-modified carbon nanotube solution, the content of the carboxyl-modified carbon nanotube is 80-120 g / L.

5. A flue gas treatment process according to claim 2, characterized in that: In the step 1, the stirring and heating reaction conditions are: 50-200 rpm, 40-50° C., 2-5 h.

6. A flue gas treatment process according to claim 2, characterized in that: In step 2, the stirring and heating reaction conditions are: 100-300 rpm, 60-80° C., 3-7 h.

7. A flue gas treatment process according to claim 2, characterized in that: In the step 3, the reaction conditions are: 100-300 rpm, 60-80° C., 1-3 h.

8. A flue gas treatment process according to claim 4, characterized in that: The preparation method of carboxyl-modified carbon nanotubes is as follows: Carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid are mixed in a mass ratio of (1-5):(8-15):(2-5), and then shaken and mixed at 30-70° C. for 3-5 hours, filtered, washed and dried to obtain carboxyl-modified carbon nanotubes.

9. A flue gas treatment process according to claim 2, characterized in that: The preparation method of the dust removal filter bag with a polymer film layer attached to the surface is as follows: The polymer is dispersed in water to prepare a 15-30% emulsion, and then the cloth is immersed in the emulsion, dipped and rolled, the rolling rate is 80-90%, and then baked at 110-125°C for 3-5 minutes to obtain the treated cloth, and then cut, sewed and assembled to obtain a dust filter bag.

10. A flue gas treatment process according to claim 9, characterized in that: The raw material of the cloth is any one of polyester, aramid, PPS, PP and PTFE.

Citation Information

Patent Citations

  • Acrylate polymer integrating water and oil repellence with flame retardancy, and preparation and application thereof

    CN101851320A

  • Polyetherimide in situ polymerization technology adopting p-phenylenediamine lossless modified carbon nano tube as heat conductive and antistatic medium

    CN105199104A

  • High-temperature ultra-clean dust removal and denitration integrated equipment

    CN110772989A

  • Non-yellowing polyurethane character filling material for rubber coating layer of fitness equipment and preparation method of non-yellowing polyurethane character filling material

    CN113861367A

  • Oil-proof finishing agent for denim fabric and preparation method of oil-proof finishing agent

    CN118756495A